Isoleucyl-tRNA synthetase 2 promotes pancreatic ductal adenocarcinoma proliferation and metastasis by stabilizing β-catenin - Yixun Jin; Xinyang Huang; Zhuoxin Wang; Berik Kouken; Qi Wang; Lifu Wang (Genes and Diseases)
Isoleucyl-tRNA synthetase 2 (IARS2), originally regarded as an enzyme ligating isoleucine to the corresponding tRNA, has been identified as an oncogene recently. However, its function in pancreatic ductal adenocarcinoma (PDAC) remains to be discovered. Here we explored the biological role of IARS2 in PDAC. Up-regulated IARS2 was found in PDAC tissues and cell lines. Kaplan–Meier survival analysis indicated a worse prognosis in patients with high IARS2 expression. CCK-8, EdU, and colony formation assays showed IARS2 overexpression enhanced PDAC proliferation, which was reduced by IARS2 knockdown. Meanwhile, IARS2 down-regulation inhibited PDAC metastasis by impeding epithelial–mesenchymal transition. These results were also supported by subcutaneous xenograft and metastasis assays in vivo. To figure out underlying mechanisms, differential and enrichment analyses were conducted and the WNT signaling pathway was discovered. Our results demonstrated that there was no significant relationship between the WNT signaling pathway key factor CTNNB1 and IARS2 at the transcription level. However, cycloheximide assays showed that IARS2 reduced the β-catenin degradation rate. IARS2 inhibited the phosphorylation of β-catenin at the Ser33/37 site and regulated downstream targets of WNT signaling including c-MYC, c-JUN, and MMP7. The enhancement of proliferation and metastasis caused by IARS2 could be reversed by MSAB, an agent that promotes β-catenin degradation. In summary, IARS2 facilitates PDAC proliferation and metastasis by stabilizing β-catenin, which leads to WNT/β-catenin activation. IARS2 serves as an underlying prognosis marker and a potential therapeutic target for PDAC.